Earnings Management Emerging Insights in Theory, Practice, and Research - Ronen, Joshua; Yaari, Varda; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
In the wake of corporate accounting scandals, the bursting of the Internet bubble, and the Sarbanes-Oxley Act$1 (Bdesigned to protect investors and consumers from such excesses$1 (B"earnings management" (the set of managerial practices and decisions that influence accounting choices and operating cash flows) has become a focal point of business strategy and academic research. Earnings Management: Emerging Insights in Theory, Practice, and Research is the most comprehensive book to date on the subject, aimed at scholars and practitioners in accounting, finance, economics, law, and public policy. Tracing two key strands of research over the past 25 years$1 (Bone focused on explaining the phenomenon and one on proposing suggestions for improving practice$1 (Bthe authors highlight theoretical and empirical contributions to the field, as well as regulatory innovations and corporate applications. Featuring numerous illustrative examples, models, and analytical techniques, the book covers such timely and important topics as: Why are earnings so important that firms feel compelled to manipulate them? What set of circumstances will induce earnings management? How will the interaction among management, boards of directors, investors, employees, suppliers, customers and regulators affect earnings management? Can truthful reporting be considered earnings management? What are the motivations for smoothing and other reporting strategies? How can scholars design empirical research to address earnings management? What are the limitations and strengths of current empirical models? Part 1 establishes the context of contemporary earnings management and presents definitions of key concepts. Parts 2 and 3 provide a review of the empirical and analytical research, respectively. Part 4 discusses the challenges of research design and considers directions for future research. An extensive bibliography lists over 2,000 publications. "Earnings management has emerged as a fundamental area of accounting research. Professors Ronen and Yaari provide a comprehensive and provocative treatment of this vital subject. This book is a must read for doctoral students, as well as established researchers, hoping to do work related to earnings management." Martin P. Loeb, Deloitte & Touche Faculty Fellow, Professor and Chair Robert H. Smith School of Business University of Maryland .s
The Importance of Earnings -- Definition of Earnings Management -- The Management -- Users -- Gatekeepers -- Truth-Telling -- Smoothing -- Maximization and Minimization -- The Accruals Process -- The Accruals Methodology -- Modifications to the Jones Model and Alternative Methodologies.
Keywords: Business; Accounting; Bookkeeping; Leadership; Finance; Economics; Management science; Microeconomics; Business and Management; Business Strategy/Leadership.; Accounting/Auditing.; Finance, general; Microeconomics; Economics, general; Electronic books